2007
DOI: 10.1016/j.nuclcard.2007.04.021
|View full text |Cite
|
Sign up to set email alerts
|

Tl-201 stress tests and homeland security

Abstract: It should be standard practice for patients to be issued information cards that indicate the potential time for triggering security radiation detectors after diagnostic cardiac procedures involving the use of Tl-201 or other radiopharmaceuticals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Multiple publications have reported that patients who were administered a radioisotope were subsequently detected and detained for triggering radiation alarms in various government and other public and private locations (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15). As a result, many of the authors suggested that patients not only should be educated about the potential for being stopped at security checkpoints but also should receive documentation helping to verify the administration of a diagnostic or therapeutic quantity of a radioisotope.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple publications have reported that patients who were administered a radioisotope were subsequently detected and detained for triggering radiation alarms in various government and other public and private locations (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15). As a result, many of the authors suggested that patients not only should be educated about the potential for being stopped at security checkpoints but also should receive documentation helping to verify the administration of a diagnostic or therapeutic quantity of a radioisotope.…”
Section: Discussionmentioning
confidence: 99%
“…Radi oactive iodine ( 131 I) is important in diagnosis and therapy for many patients with differentiated thyroid cancer. Multiple articles have reported on the detection at airports, border crossings, and other public facilities of patients who have been administered diagnostic and therapeutic activities of radioactive agents (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15). Of note, the security personnel are trying to prevent the criminal use of radiologic devices and are not trying to monitor or restrict the movement of patients emitting radiation from nuclear medicine procedures, but the detection of those patients is a well-documented phenomenon.…”
mentioning
confidence: 99%
“…Without knowing these workers received radionuclides for medical procedures, their falsely high personal monitoring badge readings could be misinterpreted as excessive occupational radiation exposure. Previous case reports highlight nuclear medicine patients setting off radiation alarms while walking through close-quarter screening stations at airports or government facilities (8)(9)(10)(11)(12)(13)(14). During the investigation of this case, the JAXPORT Risk and Safety Manager stated that a port worker had previously set off a radiation alarm while walking by detectors, due to implanted radioactive seeds (brachytherapy) for prostate cancer treatment.…”
Section: Discussionmentioning
confidence: 99%
“…With current technology, it is possible to detect 131 I activity as low as 0.01 MBq at 2–3 m (Dauer et al., 2007a). It is possible that patients treated with radionuclides could trigger alarms for ≥95 days (Dauer et al., 2007b,c). Triggering of an alarm does not mean that a patient is emitting dangerous levels of radiation, as the detectors are designed to detect levels of radioactivity far below those of concern to human health.…”
Section: Specific Radiological Protection Issuesmentioning
confidence: 99%